Hadith #2036 - Sunan al-Nasa'i - Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Ali ibn Abi Talib; Ishaq bin Mansur al-Kausaj إسحاق بن منصور بن بهرام - الكوسج; Salah bin Abi Maryam صالح بن أبي مريم الضبعي - أبو الخليل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan al-Nasa'i)
“Shall I not send you on the same mission as the Messenger of Allah sent me? Do not leave any raised grave without leveling it, or any image in a house without erasing it.”
Grade:

Hadith #3308 - Sunan al-Nasa'i - Abdullah ibn al-Harith ibn Nawfal; Ayoub al-Sakhtiyani أيوب السختياني; Muhammad bin Swa'a محمد بن سواء; Qatada قتادة; Sa'id bin Abi Sa'id; Salah bin Abi Maryam صالح بن أبي مريم الضبعي - أبو الخليل (Sunan al-Nasa'i)
“What becomes unlawful (for marriage) through breast-feeding is that which becomes unlawful through lineage.”
Grade:

Hadith #3333 - Sunan al-Nasa'i - Abu 'Alqama أبو علقمة; Abu Sa'id al-Khudri; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Qatada قتادة; Sa'id bin Abi Sa'id; Salah bin Abi Maryam صالح بن أبي مريم الضبعي - أبو الخليل; Yazid bin Zari' يزيد بن زريع (Sunan al-Nasa'i)
“Why do you do that?” We said: “A man may have a wife, and he has intercourse with her, but he does not want her to get pregnant, or he may have a concubine, and he has intercourse with her, but he does not want her to get pregnant.” He said: “It does not make any difference if you do that, for it is the matter of Al-Qadr.”
Grade:

Hadith #4457 - Sunan al-Nasa'i - Abdullah ibn al-Harith ibn Nawfal; Amr bin 'Ali bin Bahr al-Bahli عمرو بن علي بن بحر الباهلي; Hakim ibn Hizam; Qatada قتادة; Salah bin Abi Maryam صالح بن أبي مريم الضبعي - أبو الخليل; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan al-Nasa'i)
from his father, form his grandfather – the on the Day of Kahaibar, the Messenger of Allah forbade the flesh of domesticated donkeys and of al-Jallalah (animals that eat dung), and (he forbade) riding them and eating their mat.”
Grade:

Hadith #4464 - Sunan al-Nasa'i - Abdullah ibn al-Harith ibn Nawfal; Hakim ibn Hizam; Khalid bin Mahran al-Hadha' خالد بن مهران الحذاء; Qatada قتادة; Sa'id bin Abi 'Aruba سعيد بن أبي عروبة; Salah bin Abi Maryam صالح بن أبي مريم الضبعي - أبو الخليل; Shrahyl bin Aadah, Abu al-Ash'ath شراحيل بن آدة أبو الأشعث الصنعاني (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘There will come a time when a man will not care where his wealth comes from, whether (the source is) Halal or Haram.”
Grade:

Hadith #4564 - Sunan al-Nasa'i - Amr bin 'Asim al-Kalabi عمرو بن عاصم الكلابي; Hamam bin Munabbih همام بن منبه بن كامل; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Muslim bin Yasar al-'Abbassri مسلم بن يسار البصري - مسلم سكرة المصبح; Qatada قتادة; Salah bin Abi Maryam صالح بن أبي مريم الضبعي - أبو الخليل; Shrahyl bin Aadah, Abu al-Ash'ath شراحيل بن آدة أبو الأشعث الصنعاني; Ubada bin As-Samit; Ya'qub bin Ibrahim bin Sa'd يعقوب بن إبراهيم بن سعد بن إبراهيم (Sunan al-Nasa'i)
some dates from trees that were irrigated artificially were brought to the Messenger of Allah and the dates of the messenger of Allah were dates from trees that were nourished by their roots. He said: “Where did you get these from?” They said: “We bought a Sa of them for two Sa s of our dates: He said: “Do not do that, for this is not right. Rather sell your dates and but what you need of these,”
Grade:

Hadith #2154 - Sunan Abi Dawud - Abu 'Alqama أبو علقمة; Abu Sa'id al-Khudri; Qatada قتادة; Sa'id bin Abi Sa'id; Salah bin Abi Maryam صالح بن أبي مريم الضبعي - أبو الخليل; Ubaidullah bin 'Umar al-Qawariri عبيد الله بن عمر القواريري; Yazid bin Zari' يزيد بن زريع (Sunan Abi Dawud)
The aforesaid tradition has also been transmitted by Abu Hurairah through a different chain of narrators. This version adds “The fornication of ear is hearing.”
Grade: Sahih

Hadith #3348 - Sunan Abi Dawud - al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Hmam bin Yahya bin Dinar همام بن يحيى بن دينار; Muslim bin Yasar al-'Abbassri مسلم بن يسار البصري - مسلم سكرة المصبح; Qatada قتادة; Salah bin Abi Maryam صالح بن أبي مريم الضبعي - أبو الخليل; Shrahyl bin Aadah, Abu al-Ash'ath شراحيل بن آدة أبو الأشعث الصنعاني; Ubada bin As-Samit (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: Gold for gold is interest unless both hand over on the spot ; wheat for wheat is interest unless both hand over on the spot ; dates for dates is interest unless both hand over on the spot ; barley for barley is interest unless both hand over on the spot.
Grade: Sahih

Hadith #3458 - Sunan Abi Dawud - Abdullah ibn al-Harith ibn Nawfal; Hakim ibn Hizam; Hisham bin 'Abdul Malik al-Tayalasi هشام بن عبد الملك أبو الوليد الطيالسي; Qatada قتادة; Salah bin Abi Maryam صالح بن أبي مريم الضبعي - أبو الخليل; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan Abi Dawud)
When Abu Zur’ah made a business transaction with a man, he gave him the right of option. He then would tell him: Give me the right of option (to annul the bargain). He said: I heard AbuHurayrah say: The Messenger of Allah (ﷺ) said: Two people must separate only by mutual consent.
Grade: Hasan Sahih

Hadith #4285 - Sunan Abi Dawud - Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Qatada قتادة; Salah bin Abi Maryam صالح بن أبي مريم الضبعي - أبو الخليل (Sunan Abi Dawud)
The Prophet (ﷺ) said: The Mahdi will be of my stock, and will have a broad forehead a prominent nose. He will fill the earth will equity and justice as it was filled with oppression and tyranny, and he will rule for seven years.
Grade: Hasan

Hadith #4287 - Sunan Abi Dawud - Abdullah ibn al-Harith ibn Nawfal; Amr bin 'Asim al-Kalabi عمرو بن عاصم الكلابي; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Qatada قتادة; Salah bin Abi Maryam صالح بن أبي مريم الضبعي - أبو الخليل; Umm Salamah (Sunan Abi Dawud)
The other narrators mentioned “nine years” from Hisham except Mu’adh.
Grade: Da'if

Hadith #1130 - Jami' al-Tirmidhi - Abu Sa'id al-Khudri; Ahmed bin Manay' أحمد بن منيع; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Salah bin Abi Maryam صالح بن أبي مريم الضبعي - أبو الخليل; Uthman bin Muslim/Sulaiman عثمان بن مسلم/سليمان بن جرموز البتي (Jami' al-Tirmidhi)
He heard Ibn Fairuz Ad-Dhailami narrating from his father: “I went to the Prophet and said: ‘O Messenger of Allah! I accepted Islam and I had two sisters (as wives).’ So the Messenger of Allah said: ‘Chose whichever of them you will.'”
Grade:

Hadith #1242 - Jami' al-Tirmidhi - Abdullah ibn al-Harith ibn Nawfal; Hakim ibn Hizam; Muhammad bin Bashar Bindar محمد بن بشار بندار; Qatada قتادة; Salah bin Abi Maryam صالح بن أبي مريم الضبعي - أبو الخليل; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Jami' al-Tirmidhi)
That the Messenger of Allah (ﷺ) said: “Animals are not proper on credit, and there is no harm in a hand to hand (exchange).” The Hadith is Hasan Sahih.
Grade:

Hadith #3205 - Jami' al-Tirmidhi - Abd bin Hameed bin Nasr عبد بن حميد بن نصر; Abu 'Alqama أبو علقمة; Abu Sa'id al-Khudri; Hiban bin Hilal حبان بن هلال; Hmam bin Yahya bin Dinar همام بن يحيى بن دينار; Qatada قتادة; Salah bin Abi Maryam صالح بن أبي مريم الضبعي - أبو الخليل (Jami' al-Tirmidhi)
“When these Ayat were revealed to the Prophet (ﷺ): ‘Allah only wishes to remove the Rijs from you, O members of the family, and to purify you with a thorough purification (33:33)’ in the home of Umm Salamah, he called for Fatimah, Hasan, Husain, and wrapped him in the cloak, and ‘Ali was behind him, so he wrapped him in the cloak, then he said: ‘O Allah! These are the people of my house, so remove the Rijs from them, and purify them with a thorough purification.’ So Umm Salamah sai
Grade:

Hadith #3206 - Jami' al-Tirmidhi - Abu Sa'id al-Khudri; Ahmed bin Manay' أحمد بن منيع; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Salah bin Abi Maryam صالح بن أبي مريم الضبعي - أبو الخليل; Uthman bin Muslim/Sulaiman عثمان بن مسلم/سليمان بن جرموز البتي (Jami' al-Tirmidhi)
“For six months, the Messenger of Allah (ﷺ) would pass by the door of Fatimah when going to the Fajr prayer saying: ‘As-Salat O People of the house! Allah only wishes to remove the Rijs from you, O members of the family, and to purify you with thorough purification (33:33).'”
Grade:

Hadith #1693 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Hmam bin Yahya bin Dinar همام بن يحيى بن دينار; Qatada قتادة; Safinah; Salah bin Abi Maryam صالح بن أبي مريم الضبعي - أبو الخليل; Umm Salamah; Yazid bin Harun يزيد بن هارون (Sunan Ibn Majah)
that the Messenger of Allah said : “If a slave gets married without his master’s permission, he is a fornicator.”
Grade:

Hadith #2016 - Sunan Ibn Majah - Abdullah ibn al-Harith ibn Nawfal; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Muhammad bin Bashr bin al-Farafsa محمد بن بشر بن الفرافصة العبدي; Qatada قتادة; Sa'id bin Abi 'Aruba سعيد بن أبي عروبة; Salah bin Abi Maryam صالح بن أبي مريم الضبعي - أبو الخليل (Sunan Ibn Majah)
“Abdullah bin Shaddad and Abu Barzah had a dispute about paying in advance. They sent me to ‘Abdullah bin Abu Awfa to ask him about it. He said: ‘We used to make payments in advance at the time of the Messenger of Allah (ﷺ) and the time of Abu Bakr and ‘Umar, for wheat, barley, raisins and dates, to people who did not yet possess those things.’ I asked Ibn Abza, and he said something similar.”
Grade:

Hadith #2914 - Sunan Ibn Majah - Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Ali ibn Abi Talib; Muhammad bin Isma'il bin Samra محمد بن إسماعيل بن سمره الأحمسي; Salah bin Abi Maryam صالح بن أبي مريم الضبعي - أبو الخليل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Ibn Majah)
“Avoid those that are lactating.” (i.e. those from which milk is received).
Grade: